Utilization of Photo Fenton Processes with Photocatalytic Semiconductor for Treating River Water in Trinidad: A Case Study - Rikhi Ramkissoon; Krishpersad Manohar; Kiran Tota-Maharaj (Research Highlights in Science and Technology Vol. 2, 2023)
Water is a fundamental resource for human civilization, yet there is a critical water shortage happening all across the world in the twenty-first century, which is creating a problem. In some areas of underdeveloped nations, people drink water that has been extensively polluted and comes from rivers that are home to deadly diseases. The study suggests employing two techniques, photocatalytic semiconductor and Photo Fenton, as an enhanced oxidation process to get rid of different types of water impurities and offer an efficient water treatment solution. Water samples were taken from the Couva River in Trinidad and tested using the Photo Fenton process with Titanium Dioxide catalyst. To remove contaminants, the procedure was applied to the samples of river water. The physiochemical criteria that determine the properties of safe water were thus used to evaluate the reaction using both approaches. The two techniques effectively eliminated between 80 and 100 percent of the contaminants that were detected in the river sampled. Also noticed was that variations in Titanium Dioxide concentration correlated with changes in reactivity and degradation rates. Light absorption often reduces dramatically as titanium dioxide concentration rises to saturation. It was also discovered that the rate of degradation was directly correlated with light intensity. This demonstrates the technology’s potential for getting rid of water pollutants. The lower cost of the technology is a crucial benefit of this study, particularly for resource-constrained developing nations.